Kajian CIPP (Context, Input, Process, And Product) Terhadap Penyelenggaraan Pembelajaran Tingkat Sekolah Dasar di Kota Kupang Tahun Ajaran 2020-2021 - M.K.P. Abdi Keraf; R. Pasifikus Ch. Wijaya (Badan Penelitian dan Pengembangan Daerah Kota Kupang, 2022)
Research on the CIPP (Context, Input, Process, And Product) study of the implementation of elementary school level learning in Kupang City for the 2020-2021 academic year. Researchers use mixed methods research, or often called a mixed method. The number of subjects in this study were 154 school principals, 2,325 teachers, and 40,372 students and parents. The sampling technique used in this research is clustered sampling. This research was conducted for five months, starting from August to December 2021. The data collection method was carried out through structured interviews and the CIPP scale method, which consists of: the online learning CIPP scale, the offline learning CIPP scale, the limited face-to-face learning CIPP scale. The results of the research show that CIPP's study of the implementation of online PJJ at the elementary school level in Kupang City in 2020-2021 was generally carried out quite well. CIPP's study of the implementation of offline elementary school-level PJJ in the City of Kupang in 2020-2021 has been going well. CIPP's study of the implementation of Limited PTM at the elementary school level in Kupang City in 2020-2021 was carried out very well by the three groups of respondents, both students, teachers and parents. The three learning systems, namely: Online PJJ has strengths in the learning preparation component from student groups and parents, as well as in the process component from the teacher group, but online PJJ has potential weaknesses in the learning facility component and learning outcomes component according to student groups, teachers, and parents, the Implementation of Limited PTM can be used as a solution for organizing the best learning during the Covid-19 Emergency, before full face-to-face learning is implemented..